Prisoners’ Right to Rehabilitation: Micro and Macro Level Indicators for the Assessment of the Fulfilment of States’ Positive Obligation - Nikoleishvili, Karlo (Cambridge University Press (CUP), 2025)
The right to rehabilitation for prisoners is a fundamental human right recognized under international standards, imposing a positive obligation on states to ensure its fulfilment. This Article undertakes an in-depth examination of prisoners’ rehabilitation through both micro and macro lenses, examining individual experiences alongside broader societal impacts. Drawing on insights from scholars like Edgardo Rotman and Amanda Ploch, contrasting rehabilitation models are explored, highlighting tensions between institutional discipline and individual empowerment. At the macro level, rehabilitation addresses socio-economic inequalities and collective benefits, yet may overlook individual dignity from a human rights perspective. In contrast, Rotman’s humanistic model emphasizes personal insight, dialogue, and prisoners’ intrinsic rights at the micro level, fostering empowerment and a sense of responsibility. A dual perspective—from macro policy indicators to micro-level prisoner experiences—is crucial for a nuanced evaluation of rehabilitation efficacy. This exploration underscores the need for effective execution and resource allocation to uphold principles of human dignity and ensure the right to rehabilitation becomes a tangible reality for every individual within the criminal justice system.